Comparative analysis of intensive care unit prognostication scores and their renal components in predicting hospital mortality among critically ill patients - Md Ralib, Azrina; Azmi, Nurul Izzah; Mat Nor, Mohd Basri (Malaysian Society of Anaesthesiologists, 2025)
Introduction: Prognostication is essential for risk stratification in the intensive care unit (ICU). The SOFA, APACHE II, and SAPS II scores are widely used severity scoring systems, although their renal components differ. Given the association of acute kidney injury (AKI) with higher morbidity and mortality, this study aimed to evaluate these scoring systems and identify which renal component best predicts ICU outcomes. Such an insight can enhance the precision of risk assessment in critically ill patients.